How the new world became old : the deep time revolution in America - Winterer, Caroline, 1966- (Princeton modern knowledge., 2024)
"During the nineteenth century, Americans were shocked to learn that the land beneath their feet had once been stalked by terrifying beasts. T. rex and Brontosaurus ruled the continent. North America was home to saber-toothed cats and woolly mammoths, great herds of camels and hippos, and sultry tropical forests now fossilized into massive coal seams. How the New World Became Old tells the extraordinary story of how Americans discovered that the New World was not just old--it was a place rooted in deep time. In this panoramic book, Caroline Winterer traces the history of an idea that today lies at the heart of the nation's identity as a place of primordial natural beauty. Europeans called America the New World, and literal readings of the Bible suggested that Earth was only six thousand years old. Winterer takes readers from glacier-capped peaks in Yosemite to Alabama slave plantations and canal works in upstate New York, describing how naturalists, explorers, engineers, and ordinary Americans unearthed a past they never suspected, a history more ancient than anyone ever could have imagined. Drawing on archival evidence ranging from unpublished field notes and letters to early stratigraphic diagrams, How the New World Became Old reveals how the deep time revolution ushered in profound changes in science, literature, art, and religion, and how Americans came to realize that the New World might in fact be the oldest world of all." --